KANDUNGAN PROTEIN DAN ISOFLAVON PADA KEDELAI DAN KECAMBAH KEDELAI - Winarsi, Hery; Purwanto, Agus; Dwiyanti, Hidayah (Universitas Atma Jaya Yogyakarta, 2010)
The research was conducted to explore protein and isoflavone content on soy non germed and soy germed. Soybean ?slamet? was rinsed, dipped over night, drained, put in a moist room, and water sprinkled once in a while until germed. The husk of soy and soy germ were removed, and then the soy and soy germ were extracted by NaCl physiologic to become slurry. The slurry pH was arranged to 5.0, centrifugated at 10.000 rpm, and the precipitation was dryed in 70oC to obtain the soy protein and the soy germ protein flour. The levels of protein and isoflavone flour were determined. The result showed that protein content of soy was 36.5%, while protein of soy germ was 42%. The isoflavone of soy protein was 26.7 ppm, consisting of 11.5 ppm genistein, 10.2 ppm daidzein and 5 ppm glicitein, but the soy germ protein was 39.1 ppm, consisting of 14.6 ppm genistein, 16.9 ppm daidzein and 7.6 ppm glicitein. The conclusion is that germed process could increase protein and isoflavone content. The soy protein isoflavone was dominated by genistein and daidzein, while soy germ protein isoflavone was dominated by daidzein and glicitein.